A review of prevalence, complications, risk factors, knowledge assessment, selfmanagement, consciousness and treatment of diabetes mellitus in Bangladesh - Chowdhury, Wasifuzzaman (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.